2012
DOI: 10.1124/dmd.112.044636
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of a G Protein-Coupled Receptor Modulator, Including Two Major 1,2,4-Oxadiazole Ring-Opened Metabolites and a Rearranged Cysteine-Piperazine Adduct

Abstract: ABSTRACT:Metabolites of a G protein-coupled receptor modulator containing 1,2,4-oxadiazole and piperazine substructures were identified in vitro in human, rat, and dog hepatocyte incubates and in vivo in rat plasma, bile, urine, and feces by using 14 C-radiolabeled parent compound. Exposure coverage for the major circulating metabolites in humans at steady state and in preclinical species used in drug safety assessments was determined by using pooled plasma samples collected from a human multiple ascending dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Doss et al . and Gu et al . reported that the piperazine substructure in their drug candidates formed conjugated imine (α,β‐unsaturated) substructures that were trapped with GSH and subsequently underwent a ring‐contraction rearrangement.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Doss et al . and Gu et al . reported that the piperazine substructure in their drug candidates formed conjugated imine (α,β‐unsaturated) substructures that were trapped with GSH and subsequently underwent a ring‐contraction rearrangement.…”
Section: Resultsmentioning
confidence: 99%
“…Also noteworthy is the formation of M519C-M519F. With a carbonyl group on the ring, it would be highly likely to form conjugated imine (α,β-unsaturated) intermediates, such as imine amides [24] or similar structures to the reported reactive species, [20,21] which are also soft electrophiles. However, conjugation with the soft nucleophile GSH was not detected in the current work.…”
Section: Bioactivation Mechanismmentioning
confidence: 97%
See 1 more Smart Citation
“…Similarities have been demonstrated between these metabolic pathways and the pathways described for piperazines. Gu et al (56) confirmed in their research a previously reported mechanism regarding glutathione (GSH) detoxification for piperazine bioactivation products. They have analysed unusual re-arranged Cys-piperazine (cysteine-piperazine) and Gly-Cys-piperazine (glycine-cysteine-piperazine) adducts in rat and human liver microsomes.…”
Section: The Effects Of Abuse and Health Consequencesmentioning
confidence: 54%
“…Initial metabolic studies on a mGluR2 positive allosteric modulator, AZD8529, 8 using only LCMS‐based assays, completely missed a large metabolite present in human, rat, and dog liver microsomes ( AZD8529‐M1 , Scheme 1). 9 However, when the radiolabeled compound was incubated with hepatocytes in early development, the metabolite was observed. The conversion of an oxadiazole ring to a cyanamide is an unusual transformation but is precedented; similar transformations have been previously observed for L‐454560 10 and SM‐6586 11 .…”
Section: Resultsmentioning
confidence: 99%